Contemporary Oyster Reef Restoration: Responding to a Changing World - Howie, Alice H.; Bishop, Melanie J. (Frontiers in Ecology and Evolution, 2021)
Globally, there is growing interest in restoring previously widespread oyster reefs to reinstate key ecosystem services such as shoreline protection, fisheries productivity and water filtration. Yet, since peak expiration of oysters in the 1800s, significant and ongoing environmental change has occurred. Estuaries and coasts, are undergoing some of the highest rates of urbanisation, warming and ocean acidification on the planet, necessitating novel approaches to restoration. Here, we review key design considerations for oyster reef restoration projects that maximise the probability that they will meet biological and socio-economic goals not only under present-day conditions, but into the future. This includes selection of sites, and where required, substrates and oyster species and genotypes for seeding, not only on the basis of their present and future suitability in supporting oyster survival, growth and reproduction, but also based on their match to specific goals of ecosystem service delivery. Based on this review, we provide a road map of design considerations to maximise the success of future restoration projects.